2003
DOI: 10.1007/s00216-003-2110-z
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the enantiomers of substituted dihydrofurocoumarins by HPLC using macrocyclic glycopeptide chiral stationary phases

Abstract: Enantiomer separations by HPLC using the macrocyclic glycopeptides teicoplanin (Chirobiotic T), teicoplanin aglycon (Chirobiotic TAG), and ristocetin A (Chirobiotic R) chiral stationary phases (CSP) have been achieved on a unique series of potentially biologically active racemic analogues of dihydrofurocoumarin. The macrocyclic glycopeptides have proven to be very selective for this class of compound. All of the 28 chiral analogues examined afforded baseline separation on at least one of the macrocyclic glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…The effect of the carbohydrate moiety, i.e., T versus TAG, on retention and enantiomeric separation of some analytes has been discussed in previous papers [5,10]. It was shown that cleavage of the saccharides yields improved enantioresolution of most common amino acids and some other analytes for which the aglycone basket contains important sites for chiral recognition [5].…”
Section: Retention and The Hydrophobic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the carbohydrate moiety, i.e., T versus TAG, on retention and enantiomeric separation of some analytes has been discussed in previous papers [5,10]. It was shown that cleavage of the saccharides yields improved enantioresolution of most common amino acids and some other analytes for which the aglycone basket contains important sites for chiral recognition [5].…”
Section: Retention and The Hydrophobic Effectmentioning
confidence: 99%
“…It was shown that cleavage of the saccharides yields improved enantioresolution of most common amino acids and some other analytes for which the aglycone basket contains important sites for chiral recognition [5]. Both these chiral selectors (i.e., the T and the TAG) offer similar possibilities for chiral resolution of racemic analogs of dihydrofurocoumarin [10]. However, greater retention and worse efficiency were observed on the TAG column.…”
Section: Retention and The Hydrophobic Effectmentioning
confidence: 99%
“…The native cyclodextrins have been described to be inefficient at separating furocoumarin enantiomers in the reversed-phase mode [14], and this finding was in agreement with our experiments. The macrocyclic glycopeptides have shown selectivity for coumarin-based compounds [15,16], but any study employing a vancomycin-based column for the separation of warfarin enantiomers in biological samples has not been reported yet. The thermodynamic study evaluated from an experimental point of view the effect of temperature changes with four macrocyclic glycopeptide chiral stationary phase has been described [17].…”
Section: Hplc With Fluorescence Detectionmentioning
confidence: 99%
“…Purified and bonded to silica particles, they make useful chiral stationary phases (CSPs) with a broad spectrum of interactions and therefore applicability . The macrocyclic glycopeptide‐based CSPs are multimodal, meaning they are stable and efficient in normal phase (NP), reversed phase (RP), polar organic mode (POM), and polar ionic mode (PIM) . The most distinctive feature of macrocyclic glycopeptides as chiral selectors is their ionic character.…”
Section: Introductionmentioning
confidence: 99%